52nd Session of the Legal Subcommittee of the UN Committee on the Peaceful Uses of Outer Space and the Problems of International Space Law - G. P. Zhukov; O. A. Volynskaya (Московский журнал международного права)
The UN Committee on the Peaceful Uses of Outer Space 27, which consists of the Scientific and Technical and the Legal Subcommittees, is the main international centre for the interaction of states and international organizations in the area of space. Current challenges of space operations commercialization on the one hand, security and long-term sustainability on the other have forced the Committee to reassess the traditional priorities of its activity.The present article considers the results of the latest session of the Legal Subcommittee of April 2013 and their influence on the establishment of a new political and legal regime of the global space activities.